Itsbat Marriage: The Urgency and Process of Settlement in Religious Courts - Burhanuddin, Burhanuddin; Oktavia, Gifa; Taufan, Muhammad; Nurfadhilah, Nurfadhilah; Abdul Razak, Dudung (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
Our country is a country governed by law. From a legal perspective, in order to maintain order in Islamic society, marriages must be registered at the Office of Religious Affairs as stipulated in Article 2 paragraph (1) of Law No. 1 of 1974 and Article 4 of the Compilation of Islamic Law. The government provides a solution for unregistered marriages through the process of itsbath marriage. The provisions of the law that serve as the legal basis for the Religious Court to perform itsbath marriage are the explanation of Article 49 paragraph (2) point 22 of Law No. 7 of 1989 concerning Religious Courts and Article 7 paragraphs (2) and (3) letter d of the Compilation of Islamic Law. The results of the study show that isbat marriage is a request for marriage validation submitted to the Religious Court to declare the marriage valid so that it has legal force. The reasons for submitting itsbath marriage are contained in the Compilation of Islamic Law Article 7 paragraph (3), namely; the existence of a marriage in the context of settlement, the loss of a marriage certificate, a marriage that took place before the enactment of the Marriage Law No. 1 of 1974, or a marriage conducted by individuals who do not have any legal impediments to marriage under Law No. 1 of 1974. The persons entitled to apply for itsbat marriage are specified in Article 7(4) of the Compilation of Islamic Law, namely: the husband, wife, their children, and parties with an interest in the marriage. The urgency or purpose of itsbat marriage is to provide legal certainty for every marriage and to provide legal protection for the offspring of each couple. An application for itsbat marriage may be filed at the Religious Court in the place of residence of the couple seeking itsbat marriage.